Performance analysis of a 2.4 MW biogas power plant from palm oil mill liquid waste in the Sei Mangkei special economic zone - Bona Sahala Purba (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
The Biogas Power Plant (PLTBG), located in the Sei Mangkei Special Economic Zone (KEK), North Sumatra, is an effort to develop environmentally friendly renewable energy and has the potential to reduce greenhouse gas emissions. The PLTBG's performance during its first two years of operation was influenced by several factors, including electricity production, wastewater input capacity, output power, generation efficiency, and its economic value compared to PLN electricity. This study aims to process operational data of the Sei Mangkei SEZ Biogas Plant liquid waste/Palm Oil Mill Effluent (POME) Power Plant that utilizes the existing Sei Mangkei PKS liquid waste related to Performance including the capacity of the input of liquid waste/Palm Oil Mill Effluent (POME), output power. This study uses a performance approach method, stages of work activities that include several stages, namely the survey stage, data compilation stage, analysis stage, and calculation stage, data processing and conclusion. This technical analysis method uses analytical tools in the form of theoretical quantitative and qualitative models, the concept of minimizing Discharge and Waste, and the need for biogas plant environmental studies. The results of this study show that the capacity of the Sei Mangkei POM is 75 tons of FFB per hour or 325,255 tons of FFB per year. Based on fluctuations in FFB production over a 2-year period (2022-2023) in Sei Mangkei, the average production projection is 325,255 tons per year, with POME producing 65% of the average FFB production of 211,416 tons per year using the Covered In Ground Anaerobic Reactor (CIGAR) processing model.